Roadmap to developing a geometrical design guide for windcatchers - Mayhoub, Mohammed; Selim, Haitham; Abuzaid, Abdullah (Frontiers in Built Environment, 2025)
This study explores the geometrical design of windcatchers, a traditional architectural element offering a sustainable solution for natural ventilation in hot, arid climates. The growing demand for energy-efficient cooling has renewed interest in windcatchers, but their integration into contemporary architecture remains limited due to knowledge gaps and practical challenges. The study aims to: (1) offer architects practical guidelines for incorporating windcatchers into their designs, (2) create a research roadmap to address underexplored geometrical design parameters, and (3) standardize design parameters for each windcatcher component. The review identified well-studied components, such as aerodynamic advantages of curved top surfaces. It highlighted inconsistencies in literature and unvalidated findings, such as conflicting findings on the optimal outlet-to-inlet area ratio. It also revealed unexplored design parameters that require further investigation. The study developed a structured research roadmap with standardized design parameters, facilitating the creation of a comprehensive design guide for architects that ultimately enabling the more widespread and effective use of windcatchers in contemporary architectural practice.